Integrating Quality Management Into Reverse Logistics Systems - Mathew, Tom J; Subala, M. (Journal of Neonatal Surgery, 2025)
Reverse Logistics is the process of moving products from their typical final destination to Original Equipment Manufacturer and/or companies concerned in recuperation activities, in an attempt to recapture a number of used merchandise value, e.g. through resale, or for proper disposal of the item if not resalable or reusable. Reverse logistics management concerned with a variety of processes that have a direct or indirect impact on cost of quality. The development and implementation of a diagnostic tool to fully identify and measure this impact can point out the way of improving reverse logistics management and thereby leading to lower overall costs by lowering quality costs. Quality management has become an important and crucial factor among manufacturing companies. Reverse logistics and quality management are two interrelated but not frequently used aspects in the economy. The present study identifies the prospects of quality management in reverse logistics. The study gives the result that the factors influencing reverse logistics among companies are mostly social in nature. Factors influencing reverse logistics especially reduced storage and distribution cost is influenced by the level of business area. The study revealed that nature of operation, level of business area & type of products offered by the company influences the quality management in reverse logistics among the respondent companies.